A possible novel technique for intraoperative imaging of the vertebral artery during arthrodesis of the upper cervical spine. (July 2020) - Pavlov, O.; Mirchev, N.; Behr, R.
Abstract: In elderly, the fractures in C1-C2 are a common entity. Poor bone quality and wide range of motion hamper the natural bone fusion, thus making surgery often the only possible way to deal with the underlying pathology. The proximity to important neurovascular structures represents the stabilization in this segment a challenge to the surgical team. There are two major techniques, which are used to achieve a dorsal fusion in the C1-C2 Segment: Goel/Harms and Magerl techniques. The reported risk for damaging the vertebral artery in both techniques lies between 8% and 9, 5% using a C-Arm. In Goel/Harms technique lateral mass screws in C1 and pedicle screws in C2 are placed. A transarticular screw is placed on both sides C1-C2 in Magerl technique in order to achieve stabilization of the C1-C2 Segment. By using the new navigational methods for a better imaging of the bony structures (O-Arm), this risk could be reduced further down. The risk for injury of the vertebral artery using the O-Arm navigation depends on the pathology, which is operated, ranging from 0, 3% to 2%. A further problem represents the anatomical variations of the vertebral artery, of which the high-riding vertebral artery being the most important one, reported between 10 and 14, 5% of the cases according to the literature review. The novel technique for intraoperative imaging of the vertebral artery represents a fusion between an intraoperative O-Arm and intraoperative application of contrast, thus intraoperatively seeing the exact way of the vertebral artery. Also, after the insertion of the screws, a second CT scan with the O-Arm could be performed, yet again with contrast, to see whether the perfusion of both vertebral arteries is preserved. The significance of this method could bring the injuries of the vertebral artery to 0% independently on the technique, which has been used. This method could be used not only for craniocervical stabilization but also for removal of complex tumors in craniocervical junctions, whereas the vertebral artery is encompassed.